Qualification studies at SAT acceptance stage of the pharmaceutical containers washing machine - Saliy, Olena; Tarasenko, Hanna; Kuzub, Tetiana; Popova, Maria (Technologies and Engineering, 2025)
In pharmaceutical practice, glass containers are subject to mandatory cleaning before filling. The presence of dust, microorganisms or other contaminants significantly affects the quality of the medicinal product, in particular, reducing its effectiveness. Proper preparation of containers ensures the safety of medicines and their preservation throughout the entire shelf life. The purpose of the study was to evaluate the effectiveness of glass vial preparation on an automatic washing machine as part of qualification tests to confirm its compliance with production standards. The preparation of vials for bottling included disinfection, soaking, rinsing, washing, drying, depyrogenation, and sterilisation using automated washing machines. Site Acceptance Tests ensured that the equipment worked properly after installation. They included an analysis of the technical documentation, parameters of communication systems and control units of the washing machine. Residual contaminants such as sodium chloride, alkalis, and riboflavin were tested to assess the efficiency of the washing process. Based on the results, a seven-step procedure was defined, which included ultrasonic cleaning, rinsing with purified water, and a final rinse with injection water. These cycles have proven to be effective in the preparation of sterile drug containers. Recommendations for optimising process parameters, such as duration, temperature, chemical composition, and mechanical action, have helped to maximise productivity and minimise maintenance costs. A modern approach in compliance with international ISO standards ensured the high quality of vial preparation. The automated washing machine proved its efficiency, optimised the cleaning process, reduced the risk of contamination, and guaranteed the reliability of packaging preparation for sterile medicines